PS 14-79 ROLE OF ENDOGENOUS ADRENOCORTICOTROPIC HORMONE ON CIRCADIAN ALDOSTERONE RHYTHM IN PATIENTS WITH PRIMARY ALDOSTERONISM. (September 2016) - Sonoyama, Takuhiro; Sone, Masakatsu; Tamura, Naohisa; Itoh, Horishi; Nakao, Kazuwa
Abstract : Objective: We recently reported that stimulation with high-dose adrenocorticotropin (ACTH) caused different responses in terms of aldosterone secretion in aldosterone-producing adenomas (APAs) and idiopathic hyperaldosteronism (IHA) in patients with primary aldosteronism (PA). However, the role of endogenous ACTH in aldosterone secretion in PA has not been systematically evaluated. In this study, we examined diurnal changes in plasma aldosterone concentration (PAC), and changes in PAC after dexamethasone administration in patients with suspected PA, in order to evaluate the effect of endogenous ACTH on aldosterone secretion. Design and Method: Seventy-three patients admitted to Kyoto University Hospital with suspected PA were included. Patients were classified into non-PA, IHA, and APA groups according to the results of captopril challenge test and adrenal venous sampling. PAC at 09.00 (PAC0900 ), 23.00 (PAC2300 ), and after 1 mg dexamethasone suppression (PACdex ) were measured and compared among the three groups. The PAC2300 /PAC0900, and PACdex /PAC0900 ratios were also analyzed. Results: PAC2300 and PACdex were lower than PAC0900 in all three groups. There were no significant differences in PAC2300 /PAC0900 among the three groups. However, PACdex /PAC0900 was significantly lower in the APA group compared with the non-PA and IHA groups. Conclusions: The results of this study indicate that aldosterone secretion in APA patients is more strongly dependent on endogenous ACTH than in IHA and non-PA patients. The results also suggest that factors other than ACTH, such as clock genes, may cause diurnal changes in aldosterone secretion in IHA and non-PA patients.